2007
DOI: 10.3171/jns.2007.106.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for facial schwannoma

Abstract: In summary, radiosurgery was found to be a very useful method of treating facial schwannoma, for both tumor control and functional control. Radiosurgery should therefore be the treatment of first choice for facial schwannomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 17 publications
2
46
0
1
Order By: Relevance
“…Recently, radiotherapy has been advocated as a less invasive alternative primary treatment in patients with FNSs [Mabanta et al, 1999;Kida et al, 2007;Litre et al, 2007;McClelland et al, 2007;Hillman et al, 2008;Madhok et al, 2009;Nishioka et al, 2009, Wilkinson et al, 2011. The efficiency of radiotherapy in long-term tumor control is still unknown, and further studies with longer follow-up are necessary [Marzo et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, radiotherapy has been advocated as a less invasive alternative primary treatment in patients with FNSs [Mabanta et al, 1999;Kida et al, 2007;Litre et al, 2007;McClelland et al, 2007;Hillman et al, 2008;Madhok et al, 2009;Nishioka et al, 2009, Wilkinson et al, 2011. The efficiency of radiotherapy in long-term tumor control is still unknown, and further studies with longer follow-up are necessary [Marzo et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…These procedures comprise subtotal tumor removal, facial nerve decompression, and fascicle preservation surgery. Recently, radiotherapy has been advocated as a primary therapeutic option in patients with FNS [Kida et al, 2007;Litre et al, 2007;McClelland et al, 2007;Hillman et al, 2008;Madhok et al, 2009]. During the last decade various management algorithms have been developed in order to standardize treatment of FNS [Marzo et al, 2009;Bäck et al, 2010;Wilkinson et al 2011;Gross et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…23 During the last 3 decades, SRS has emerged as another possible treatment option. There are several reports that showed the safety and efficacy of SRS for patients with FNSs, 2,3,5,17,18,21,22 but the reported studies generally included a small number of patients. To our knowledge, ours is the largest study to date of FNSs treated with SRS.…”
Section: Discussion Treatment Optionsmentioning
confidence: 99%
“…2,6,10,15,21,29,48,49,55 Sheehan and colleagues 45 have reported excellent results using GKS in 26 patients with trigeminal schwannomas, and Hasegawa and associates 14 found similar results in 37 patients. Kida et al 18 reported a 100% tumor control rate of facial neuromas after a mean follow-up of 31 months with GKS. Litre et al 28 reported that 10 of 11 patients with facial schwannomas were stable after this same treatment.…”
Section: Schwannomasmentioning
confidence: 99%